PENGARUH PENDIDIKAN KEWIRAUSAHAAN, EFIKASI DIRI DAN KEBUTUHAN AKAN PRESTASI TERHADAP INTENSI KEWIRAUSAHAAN MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN SURAKARTA - Rahmawati, Rahmawati (El-Hayah, 2017)
Abstract : This research is conducted to know the effect of entrepreneurship education, self efficacy and necessity for achievement of students’ entrepreneurship intention at Faculty of Economics and Islamic Business of IAIN Surakarta in 2017, either partially or simultaneously.This research used quantitative method. The study population was 986 people who were students of 7th, 9th, 11th and 13th semester at Faculty of Economics and Islamic Business of IAIN Surakarta. Data collection used questionnaires given to the sample of 189 respondents. The data were processed through the requirements test and hypothesis test used SPSS 21 program.The results of this study indicate that all items questionnaire are declared valid and reliable. Based on multiple linear regression analysis, it can be concluded that: 1) entrepreneurship education has a positive effect on entrepreneurial intention of 0.360; 2) self efficacy has a positive effect on entrepreneurial intention of 0.153; 3) necessity for achievement has a positive effect on the entrepreneurial intention of 0.183; 4) entrepreneurship education and self efficacy simultaneously affect the entrepreneurial intentions by 20%; 5) entrepreneurship education and necessity for achievement simultaneously affect the intention of entrepreneurship by 20.8%; 6) self efficacy and necessity for achievement simultaneously affect the intention of entrepreneurship by 17.4%; 7) entrepreneurship education, self efficacy and necessity for achievement simultaneously affect the entrepreneurial intentions of 62.8%